Eye tracking and cardiovascular measurement to assess and improve sporting performance - Crowe, E. M.; Wilson, M. R.; Harris, D. J.; Vine, S. J. (Advances in mental skills training, 2021)
One of the difficulties of working in applied sports psychology is the lack of objective data to help understand the psychological components of an athlete`s performance. This may be one of the primary explanations for the disparity between how important coaches and athletes report psychological elements of elite performance to be and how much they invest in tracking and supporting such elements. In this chapter, we discuss two objective psychophysiological measures that provide valuable insight into the psychology of performing under pressure in elite sports and can address the need for objective data to support athlete performance. Both measures - eye tracking and cardiovascular reactivity - have considerable evidence underpinning their efficacy in research environments. We discuss some practical issues that require consideration when using such measures in applied sports settings and report a case study. Combining these measures enables an in-depth and objective investigation into the complex interplay between visuomotor and physiological factors in the sporting environment. Eye tracking and impedance cardiography are effective, relatively cheap, and noninvasive techniques that practitioners can use in applied sporting settings to gain valuable insights into an athlete`s visuomotor control and cardiovascular reactivity. This chapter outlined the benefits of obtaining objective data that can provide insight into the psychological state of athletes in applied settings. The case study demonstrated the value of using such techniques to collect large volumes of data that enable individualised, in-depth insights into an athlete`s performance. We also discussed the challenges of utilising these techniques to highlight factors that require consideration prior to data collection, with a view to supporting practitioners who wish to implement objective measures more effectively in an applied setting.